Tranformation and needs room layout design that determine the footwear industry Function in residential Jakarta - Putriaz Rahmi (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2016)
The purpose of this reserach is to provide design ideas of shoes home industry by designing the layout that can acommodate the transformation and space needed working & living area. The research’s method based on the phenomenon in the shoes home industry starting from surveying the object which is Perkampungan Industri Kecil (PIK) Penggilingan and understanding the fundamentals points of shoes home industry in terms of transformation, space requirements, and natural lighting & ventilation. The pattern of object’s transformation used for determine the organization of space that can be considered for designing the layout. Space requirement analyzed according to the standard of space. Lighting & natural ventilation analyzed with ecotect simulation according to the standard of health’s minister. The research concluded that the pattern of transformation on the object by level of transformation should be done by extension. In spatial transformation, the design should adapt to makes change of space requirement, especially for the expansion of flexible and residential area. In configurational transformation, service area should be considered in layout design because its fixed position. Some of residential area can be combined with production area in the very small home industry. In the small home industry, some of space can be multifunctional, but there should have a separation between residential and production area. Space on the object needs some adjustments based on standard of space requirements. Some of space can be multifunctional and used portable furniture depends on activity and time-used. Working maps of production area should be arrange using spatial patterns based on the flow of production process. Natural lighting and ventilation should be adjusted to the lighting standard (1000 lux for upper area, 300 lux for bottom area) and thermal comfort (21-30°C).